2020
DOI: 10.3390/polym13010032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Furfurylation on Hierarchical Porous Structure of Poplar Wood

Abstract: Some wood properties (such as permeability and acoustic properties) are closely related to its hierarchical porous structure, which is responsible for its potential applications. In this study, the effect of wood impregnation with furfuryl alcohol on its hierarchical porous structure was investigated by microscopy, mercury intrusion porosimetry and nuclear magnetic resonance cryoporometry. Results indicated decreasing lumina diameters and increasing cell wall thickness of various cells after modification. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The reason for this was speculated to be that latewood has a higher cell wall/cavity ratio than earlywood, which constrained its ability to accommodate exotic modifiers. Moreover, the cell wall pits and the perforation between tracheids are more inclined to be aspirated than earlywood, resulting in a significantly lower WPG in latewood [16]. Combined with the ImageJ results, the cell wall of earlywood swelled from 2.68 to 5.41 µm after modification, resulting in the 119.42% higher WPG than that of latewood under the same treatment conditions.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 84%
“…The reason for this was speculated to be that latewood has a higher cell wall/cavity ratio than earlywood, which constrained its ability to accommodate exotic modifiers. Moreover, the cell wall pits and the perforation between tracheids are more inclined to be aspirated than earlywood, resulting in a significantly lower WPG in latewood [16]. Combined with the ImageJ results, the cell wall of earlywood swelled from 2.68 to 5.41 µm after modification, resulting in the 119.42% higher WPG than that of latewood under the same treatment conditions.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 84%
“…Nevertheless, the membrane formed by these micropores has been reduced into a deep groove, which is essential for excellent water treatment performance. Natural wood has a hierarchical structure with diverse distribution and connectivity of pores in different directions (Yin et al 2015;Shen et al 2021;Ru et al 2023), which provides more contact for water filtration. The water treatment performance of the twodirectional-flow wood filter with different thickness was compared.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of spatial polymer networks of used material in the lumens of wood cells or even in the micropores of cell walls may explain decreases in WA and S of treated wood. Shen et al 2021 reported that the porosity and pore volume of furfurylated woods decreased with raising WPG. On the other hand, the possibility of sporadically covalent bonds of F + U / M resin with the polymers of cell walls should not be overlooked.…”
Section: Physical Propertiesmentioning
confidence: 99%